2020
DOI: 10.1039/d0gc00208a
|View full text |Cite
|
Sign up to set email alerts
|

Haber-independent, diversity-oriented synthesis of nitrogen compounds from biorenewable chitin

Abstract: A chitin-sourced 3-aminocyclopentenone building block is an effective platform for the diversity-oriented synthesis of nitrogen compounds in processes independent of Haber ammonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 97 publications
0
41
0
Order By: Relevance
“…This work highlights the feasibility to produce value-added chiral amino sugar from 3A5AF. Very recently, Pham et al [49] reported the synthesis of 3-aminocyclopentenone from 3A5AF via Piancatelli rearrangement, and the further conversion gave several 3-aminocyclopentanones, 4-aminocyclopentene-1,3-diones, and a 4-aminocyclopenteneone. Notably, the authors investigated the transformation of two 4aminocyclopentene-1,3-diones to N-scaffolds through a one-or two-step procedure, and the prepared chemicals, such as aminated bicyclic ethers, pyridines, bicyclic pyrrolidines, and isoquinolines, can be used in medicinal chemistry directly.…”
Section: Conversion Of Nag-derived 3a5af To Heterocyclic Compoundsmentioning
confidence: 99%
“…This work highlights the feasibility to produce value-added chiral amino sugar from 3A5AF. Very recently, Pham et al [49] reported the synthesis of 3-aminocyclopentenone from 3A5AF via Piancatelli rearrangement, and the further conversion gave several 3-aminocyclopentanones, 4-aminocyclopentene-1,3-diones, and a 4-aminocyclopenteneone. Notably, the authors investigated the transformation of two 4aminocyclopentene-1,3-diones to N-scaffolds through a one-or two-step procedure, and the prepared chemicals, such as aminated bicyclic ethers, pyridines, bicyclic pyrrolidines, and isoquinolines, can be used in medicinal chemistry directly.…”
Section: Conversion Of Nag-derived 3a5af To Heterocyclic Compoundsmentioning
confidence: 99%
“…[23,262] 18) and ()-oxycodone (19). [50][51] Scheme 4: Chitin/Chitosan-derived starting material 22 and products thereof by Sperry et al [59,268] Nevertheless, nitrogen-containing fine chemicals remain a challenging task for xylochemical synthesis approaches, as they are not directly attainable from lignocellulosic biomass. To this end, the Sperry group has used chitin (20), the second-most abundant biopolymer, as a cheap natural source of nitrogen, to show a proofof-concept synthesis of the anticancer alkaloid proximicin A (23) in seven steps.…”
Section: Xylochemical Synthesis Approachesmentioning
confidence: 99%
“…With this strategy, the group was also able to demonstrate the synthesis of various 3-aminocyclopentanones, 4aminocyclopentene-1,3-diones and a 4-aminocyclopentenone by applying the chitin-derived furfural 22 in a Piancatelli-like rearrangement (Scheme 4). [268] 58). [60,269] By applying acidolysis strategies to lignin, the Barta group managed to directly afford three different substance classes of aromatic compounds that can be used as valuable aromatic monomers in further synthesis (Scheme 5).…”
Section: Xylochemical Synthesis Approachesmentioning
confidence: 99%
“…The industrial production of nitrogen‐containing chemicals requires large amounts of ammonia (NH 3 ). The Haber‐Bosch process used to produce NH 3 consumes huge amounts of energy because it needs to break the strong N≡N triple bond in nitrogen, and also consumes about 50 % of the H 2 supply [8] . Considering the high cost and pollution of NH 3 synthesis, manufacturing nitrogen‐containing chemicals from nitrogen‐containing biomass feedstock such as microalgae will be more sustainable and meaningful [9] .…”
Section: Introductionmentioning
confidence: 99%